Hong Kong protests and tourism: Modelling tourist trust on revisit intention - Poon, W. C.; Koay, Kian Yeik * (Sage, 2021)
Drawing on prospect theory (the subgroup of behavioural economics) and information integration theory, this study proposes and empirically tests a research model exploring the influence of tourist trust on tourists’ revisit intention through the mediating effect of attitudes in the Hong Kong (HK) protest context. A series of protests commenced on 3 April 2019 against the Extradition Law Amendment Bill Movement have severely impacted the HK tourism industry as the destination may deem to be unsafe by tourists to revisit. This study is important because HK protests happened at least 10 protests per month from April to December 2019, which have brought an adverse impact on the tourism industry. Using a survey method, we collected 176 data from those who had prior experience visiting HK, and data were analysed using partial least squares structural equation modelling. Overall, the findings demonstrate that attitudes mediate the effect of tourists’ trust on revisit intention, but no direct effect of trust on revisit intention ascribe to hazard protests. Recognizing greater uncertainty arises following reports from media that prominently inform tourists’ decision-making, and how selfperceived trust influences attitudes on hazards offers intriguing managerial and practical implications for managers and policymakers. Besides, theoretical implications and directions for future research are presented.